Al-Quran sebagai Sumber Epistemologi Islam: Analisis Pendekatan Tafsir dan Studi Islam - Neldayenti, Neldayenti; Mulyani, Tati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study analyzes the Al-Qur'an as a source of Islamic epistemology through the synergy of tafsir approaches and contemporary Islamic studies. Employing a qualitative descriptive-analytical method with library research and Islamic hermeneutics, the research examines three key problem formulations: the concept of tafsir principles, aspects and methods of Qur'anic understanding, and its epistemological perspective. Data were gathered from relevant articles and research findings aligned with the study's title. The results demonstrate that tafsir principles (linguistic, asbab an-nuzul, tafsir bi al-Qur'an) preserve the purity of revelatory meanings, while holistic aspects (linguistic, historical, spiritual, social, epistemological) and methods (tahlili, maudhu’i, hermeneutic) ensure contemporary relevance. Epistemologically, the Al-Qur'an integrates revelation-reason-empiricism with tawhid as the unifying principle of knowledge, addressing secularization challenges through Fazlur Rahman's double movement and Al-Attas's ta’dib framework. The findings affirm the Al-Qur'an as a living source of knowledge (matan ilmi hidup) capable of reconstructing Islamic civilization in the digital era. This research contributes to the development of moderate thematic tafsir in line with the 2025 Ministry of Religious Affairs recommendations.